Influence of third particle on the tribological behaviors of diamond-like carbon films - Bai, Lichun (2018)
Tribological mechanisms of diamond-like carbon (DLC) films in a sand-dust environment are commonly unclear due to the complicated three-body abrasion caused by sand particles. This study investigates the three-body abrasion of the DLC film via molecular dynamics simulations. The influence factors such as the load, velocity, shape of the particle and its size are considered. It has been found that the friction and wear of the DLC film are determined by adhesion at a small load but dominated by both adhesion and plowing at a large load. A high velocity can increase the friction of the DLC film but decrease its wear, due to the response of its networks to a high strain rate indicated by such velocity. The shape of the particle highly affects its movement mode and thus changes the friction and wear of the DLC film. It is found that a small-sized particle can increase the friction and wear of the DLC film by enhancing plowing. These unique tribological mechanisms of the DLC film can help to promote its wide applications in a sand-dust environment.